2011
DOI: 10.1270/jsbbs.61.101
|View full text |Cite
|
Sign up to set email alerts
|

A proposed selection criterion for drought resistance across multiple environments in maize

Abstract: Drought resistance is a complex quantitative trait, involving interactions of many metabolic pathways related to stress-resistant genes. Identification of a standard evaluation assay has been the most pressing problem for selection of drought-resistant genotypes and ultimately for elucidating the internal genetic mechanisms. A field phenotypic investigation was performed on more than 20 morphological traits and grain yield and its components for 201 Chinese common inbred maize (Zea mays L.) lines under water d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Here again the gradual increase in water deficit conditions regularly reduced the seed yield for all three genotypes. These findings corroborated the results reported by Hao et al [23] who stated that irrigation stress may reduce the mungbean seed yield and affect WUE. WUE: the major object of this research and the aggregate of all physiological, genetic and phonological mechanisms of plants under certain situations was recorded as highest for VC-2010 and I4 combination followed by Kawmay-1.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Here again the gradual increase in water deficit conditions regularly reduced the seed yield for all three genotypes. These findings corroborated the results reported by Hao et al [23] who stated that irrigation stress may reduce the mungbean seed yield and affect WUE. WUE: the major object of this research and the aggregate of all physiological, genetic and phonological mechanisms of plants under certain situations was recorded as highest for VC-2010 and I4 combination followed by Kawmay-1.…”
Section: Resultssupporting
confidence: 92%
“…Crop plants are usually under stress at one time or another and plant species able to withstand such stresses have great economic potential [22]. Use of drought tolerant species is one of the effective strategies used to cope with water deficit stress wisely, as some plants species are able to withstand such stresses [21][22][23]. The proper application of deficit irrigation practices can generate significant saving in irrigation water supplies [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Five drought resistance indices including stress tolerance index (STI), mean production (MP), geometric mean production (GMP), stress susceptibility (SSI), and yield stability index (YSI), were calculated using the following relationships (Fischer, Maurer 1978;Rosielle, Hamblin 1981;Fernandez 1992;Gavuzzi et al 1997): where Y p is particular yield in non-stress conditions, Y s is particular yield in stress conditions, Y p is mean yield in non-stress conditions, Y s is mean yield in stress conditions. The integrated selection index (SI) was calculated according to Hao et al (2011) on the basis of the obtained results from factor analysis for agro-morphological traits under non-stress and water deficit stress conditions using the following steps:…”
Section: Discussionmentioning
confidence: 99%
“…These agronomic traits are simple criteria for drought tolerance, and using these traits in integrated selection criterion (SI) decreases the risk of selection of tolerant lines. Likewise, Hao et al (2011) and used the integrated selection index (SI) to screen tolerance genotypes of corn and barley under normal and stress conditions, respectively. Principal components analysis showed that PCA1 and PCA2 explained 98.2% of the total yield variation, hence the first and second component were named as yield potential and stress susceptibility, respectively.…”
Section: New Drought Tolerance Indicator For Screening Barley Linesmentioning
confidence: 99%
See 1 more Smart Citation